Effects of a clostridial bacterin-toxoid administered subcutaneously at the base of the ear on stocker heifer performance, testosterone serum concentrations, and infrared thermal characteristics of the injection site and adjacent tissues - J.M. Sargeant; M.F. Spire; S.I. Paisley; J. Ernest Minton; Dale A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2000)
A 129-day field study was conducted to evaluate the effects of a clostridial bacterintoxoid administered subcutaneously at the base of the ear on heifer calf performance, surfaceear temperature, and testosterone concentration. Two hundred previously non-implanted heifers averaging 372 lb were assigned to one of four treatments: 1) α-7 (clostridial toxoid) in left neck, Synovex-H in left ear (NL); 2) α-7 in left neck, Synovex-H in right ear (NR); 3) α-7 in right ear, Synovex-H in opposite ear (OP); and 4) α-7 in right ear, Synovex-H in same ear (SM). On day 7, the right ear of each heifer was thermographically imaged. On trial days 7, 28, 59, and 87, jugular blood samples were collected to determine if placement of the clostridial vaccine reduced serum concentration of testosterone. Although vaccinating in the base of the ear increased (P.84) for heifers implanted in the right ear and vaccinated in the same side ear or neck.
Keywords: Cattlemen& #x27; s Day; 2000; Kansas Agricultural Experiment Station contribution; no. 00-287-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 850; Beef; Infrared; Injection site; Growth implant; Heifers